Understanding Household Demand for Savings Services Offered by MFIs - Arora, Kishor (Journal of Global Economy, Business and Finance, 2025)
Financial inclusion for the urban poor involves providing both credit and savings services, yet many are reluctant to use formal financial services due to psychological barriers and a lack of knowledge. This study investigates the demand for Microfinance Institutions' (MFI's) savings services among households in Delhi slums. Based on primary data from 150 households, the findings reveal a strong demand for MFI saving services due to their accessibility, trust, and flexibility. The study highlights the importance of tailored financial products in promoting financial inclusion and suggests that MFIs can play a crucial role in meeting the saving needs of the urban poor.